Climatological studies of lapse rates during summer months vis-à-vis All India Summer Monsoon Rainfall (MAUSAM, 2008)
The combined mean normal lapse rates for 0000 and 1200 UTC for 35 Radiosonde (RS) stations based on the period 1971-99 during the summer months (March to May) were worked out for standard levels and analysed.  To know whether any relationship exists between the distribution of summer lapse rates and the all India summer monsoon rainfall (June to September),  the mean lapse rates for three good monsoon years and six deficient years during the same period were worked out separately and the Lapse Rate Anomalies (LRAs) were examined in detail.  In excessive monsoon rainfall years the LRAs were generally negative (instable atmosphere) during summer months (March-May) in the lower and middle troposphere and the anomalies were positive in the upper troposphere.  In the deficient monsoon years, the case is reverse i.e., LRAs were positive in the lower troposphere (inhibiting the convective activity) while they were negative in the middle and upper troposphere.  The same results were noticed in the recent worst monsoon year 2002 and bad monsoon year 2004. The LRAs thus give signals in the months of March to May regarding the ensuing monsoon rainfall qualitatively and can be used as one of the tools for long range forecasting.